Stimulasi Kesantunan Berbahasa Anak Usia Dini di PAUD Hauriyah Halum, Padang - Muthie, Imam; Yaswinda, Yaswinda (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
The purpose of this study was to describe how the stimulation of early childhood language politeness in class B1 children at Hauriyah Halum PAUD Padang was carried out. This research is a descriptive approach with qualitative methods. The research was conducted from April 19 to May 19 2019. Researchers used teachers and parents as informants. The way to collect data that the researcher uses is observation, interview, and documentation, while the data analysis technique is done using data triangulation techniques. This study found that the development of children's language politeness in Hauriyah Halum PAUD was carried out through the application of donated duo baleh in accordance with Minangkabau culture and integrated in the learning process, the center. Every activity of developing language politeness is carried out through the process of habituation until it is finally embedded properly for the child. The center which is the focus of politeness-language research is the beam center, natural center, Islamic center, arts center and preparation center. The teacher carries out the development of language politeness by providing simulations through various types of activities in the classroom and outside the classroom. The teacher uses a variety of methods in implementing the development of children's language politeness, namely using, direct practice methods, demonstration methods, and methods of assigning assignments. Then it can be concluded from this study that the implementation of stimulation of speaking politeness in early childhood at PAUD Hauriyah Halum Padang has gone well in accordance with the principles of Minangkabau cultural politeness.